Development of nanocomposite 3D-scaffolds for bone repair - Mahmood, Saffanah Khuder (2017)
The demands for applicable tissue-engineered scaffolds that can be used to repair load-bearing segmental bone defects (SBDs) are vital and increasing. Significant bone problems named trauma, deformity and tumors leave the patients under the pressure of surgical complications, high cost, risk of infection, donor shortage and slow healing process. The main objective of this study is to develop porous nanocomposite scaffold from cockle shell nanopowder for SBD repair. In this study, 9 different combinations of nanocomposite porous scaffolds were fabricated using various proportion of cockle shell-derived CaCO3 aragonite nanoparticles, gelatin, dextran and dextrin. The scaffold then used for repairing critical-size bone defect (2 cm) that made on the shaft of radial bone of 16 adult, male New Zealand White rabbits which divided into four groups (n=4): Group A (control), Group B (scaffold 5211), Group C (5211GTA+Alginate) and Group D (5211PLA). The defect site implanted with scaffold was assessed for 8 weeks by means of radiography, hematology, biochemistry, grossly and histology. The micron sized cockle shell-derived CaCO3 powder obtained (75 μm) was transformed into nanoparticles using mechano-chemical and ball mill (top-down) methods of nanoparticle synthesis with the presence of surfactant BS-12 (dodecyl dimethyl bataine). The phase purity and crystallographic structures, the chemical functionality and the thermal characterization of the scaffolds’ powder were analyzed using Fourier Transform InfraRed (FTIR) spectrophotometer, Powder X-Ray Diffractometer (PXRD) and Differential Scanning Calorimetry (DSC), respectively. Characterizations of the scaffolds were assessed by Scanning Electron Microscopy (SEM), porosity test, swelling test, water absorption test, degradation manner and mechanical test. The cytocompatibility of the scaffolds was assessed in terms of cell attachment, alkaline phosphatase (ALP) concentration, cell proliferation and capability to form mineralized bone nodules. The tests were conducted throughout In vitro cell culture using human Fetal OsteoBlast cells line (hFOB). Top-down methods produced cockle shell-derived CaCO3 aragonite nanoparticles having size range of 15.94-55.21±6 nm which were determined using Field Emission Scanning Electron Microscopy (FESEM) and Transmission Electron Microscopy (TEM). The aragonite form of calcium carbonate was identified in both PXRD and FTIR for all scaffolds, while the melting (Tm) and transition temperatures (Tg) were identified using DSC with the range of Tm 62.41-75.51°C and Tg 229.38-232.58°C. Engineering analyses showed that scaffolds possessed a 3D interconnected homogenous porous structure with pore sizes 8-526 μm, porosity 6-97%, mechanical strength 4-65 MPa, Young’s Modulus104-296 MPa and enzymatic degradation rate 16-67% within 2, 4 and 10 weeks. The biological evaluation also showed that all scaffolds did enhance the osteoblast proliferation rate and improved the osteoblast function as demonstrated by the significant increase in ALP concentration. Radiographic examination showed new trabecular bone formation that signifies the bone healing/regeneration. This occurred in the defects edge as well as in the middle within one month which involved osteogenesis that moved within the central region and margin of the scaffold implant. This was attained with negligible tissue responses to a foreign body which was seen through hematology, biochemistry and histopathological analyses results. Grossly and histologically, after 8 weeks post-implantation the quantity of mature bone increased forming whole bone. The new bone tissue that was produced was successively matured within time as anticipated with increased mature cortical bone development and regeneration. Animal experiment revealed that the material used was able to resist load-bearing situations in extended usage without material breaking or generating stress protective effects to the bone of the host. This work signifies a key development in the healing of artificial bone grafts and suggests that the biomaterial of the grafted scaffold could possess great potential in prospective clinical uses where regeneration of bone is necessary.